Language Policy Implementation For Service Delivery: A Case Study of Ekurhuleni Metropolitan Municipality in South Africa - Khayelihle Phumlani Nkosi; Thabo Ditsele (E-Journal of Humanities, Arts and Social Sciences)
South African local authorities (i.e., local government sector) have a responsibility to develop and strengthen Southern Bantu languages as prescribed by the country’s Constitution. This was done to make sure that all official languages in the country are equitably used and developed as scientific languages in all government spheres. The purpose of this study was to examine challenges faced by the community in terms of implementing language policy for service delivery at a municipality level. The study selected Ekurhuleni Metropolitan Municipality (EMM) in Gauteng as a research site.This was a qualitative study, and document analysis and interviews were utilised to gather data from the selected participants. The study found that despite EMM having a multilingual language policy, it overwhelmingly favoured using English at the expense of other languages it gave official status. Hence, the municipality did not do justice to most of its residents who cannot communicate in English as a home language, thereby did not service them well, at least as far as communicating with them was concerned. EMM has taken a step in the right direction by giving Southern Bantu languages official status and such a step can be enhanced by developing clearly spelt out language policy implementation strategies that unambiguously outline how it will further develop isiZulu, Xitsonga, Tshivenda and Sesotho. Official languages chosen by EMM had also been chosen by its neigbouring metropolitan municipalities in Gauteng, that is, Johannesburg and Tshwane, and by collaborating with the two, EMM can improve its offering to its residents by communicating with them more meaningfully in those Southern Bantu languages.